Effectiveness of a job vacancy referral scheme - Joost Bollens; Bart Cockx (IZA Journal of Labor Policy, 2017)
The public employment service (PES) makes use in many countries of vacancy referrals as to facilitate the matching between unemployed workers and vacancies. Based on a 'timing-of-events' approach to control for selective participation, this study evaluates whether this policy instrument enhanced the transition to employment in Flanders (region in northern Belgium). Three referral types are distinguished: (1) referrals actively matched by a caseworker by phone or by e-mail; (2) automatic referrals, in which the match is accomplished by a software without caseworker intervention; and (3) invitations, in which the referral is transmitted to the unemployed in a meeting with a caseworker. All three referral instruments are found to be effective, even many months after the transmission of the referral: the first and third referral types more than triples, respectively, double the transition rate to employment both in short- and long-run, while the automatic referrals enhance this rate by 50% in the first 2 months and double it in the long-run.
Keywords: C41; J63; J64; J65; J68; 330; Vacancy referral; Active labor market policy; Evaluation; Timing-of-events method; Unemployed; Transition to employment